2021
DOI: 10.1186/s12886-021-02131-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgically induced astigmatism between anterior and total cornea in 2.2 mm steep meridian incision cataract surgery

Abstract: Background This study aimed to compare surgically induced astigmatism (SIA) on the anterior and total cornea during cataract surgery through a 2.2 mm steep meridian incision. Methods The study included 69 left eyes of 69 patients who had undergone cataract surgery. The 69 eyes were classified into three subgroups according to the preoperative steep meridian. Following phacoemulsification, an intraocular lens was inserted into the bag. The keratomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This is mostly caused by the steepening of the corneal back surface (0.04 dpt), whereas flattening of the corneal front surface is very low (0.01 dpt). In 2021 Yoon et al studied SIA based on measurements made with an automated keratometer and a Scheimpflug tomographer [26]. They found that in their study population including 69 eyes there was a very slight statistically non-significant decrease in the power of the anterior surface (on average -0.02 dpt) and in the power of the posterior surface (on average -0.01 dpt).…”
Section: Discussionmentioning
confidence: 99%
“…This is mostly caused by the steepening of the corneal back surface (0.04 dpt), whereas flattening of the corneal front surface is very low (0.01 dpt). In 2021 Yoon et al studied SIA based on measurements made with an automated keratometer and a Scheimpflug tomographer [26]. They found that in their study population including 69 eyes there was a very slight statistically non-significant decrease in the power of the anterior surface (on average -0.02 dpt) and in the power of the posterior surface (on average -0.01 dpt).…”
Section: Discussionmentioning
confidence: 99%
“…The toric IOL power was derived based on the “real power” value of the Casia 2 considering the corneal front and back surface based on a thick lens model, and the toric lens markers were aligned to the steep axis of the “real power.” After paralimbal 2.2-mm (astigmatism-neutral) microincision from the temporal side, the anterior chamber was filled with a cohesive ophthalmic viscosurgical device and the creation of a continuous curvilinear capsulorhexis (CCC) was slightly smaller than the IOL optic diameter (approximately 5.25 mm). 8,24–28 After a standard phacoemulsification procedure, the Vivinex tIOL was inserted and aligned with its marker at the steep corneal meridian (CASIA2) and the CCC and both paracenteses were hydrated.…”
Section: Methodsmentioning
confidence: 99%
“…After paralimbal 2.2-mm (astigmatism-neutral) microincision from the temporal side, the anterior chamber was filled with a cohesive ophthalmic viscosurgical device and the creation of a continuous curvilinear capsulorhexis (CCC) was slightly smaller than the IOL optic diameter (approximately 5.25 mm). 8,[24][25][26][27][28] After a standard phacoemulsification procedure, the Vivinex tIOL was inserted and aligned with its marker at the steep corneal meridian (CASIA2) and the CCC and both paracenteses were hydrated.…”
Section: Dataset and Surgical Detailsmentioning
confidence: 99%
“…The steep-meridian corneal relaxing incision (SM–CRI) is made at the steep meridian of the cornea [ 6 ]. The basic principle is that the relaxing incision of the cornea flattens the steep meridian and steepens the flat meridian to reduce corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%